2014
DOI: 10.1097/meg.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Does the extent of lymphadenectomy, number of lymph nodes, positive lymph node ratio and neutrophil–lymphocyte ratio impact surgical outcome of perihilar cholangiocarcinoma?

Abstract: Extended lymphadenectomy patients (≥20 LNs) had worse OS when compared with those with more limited (<20 LNs) resection. An LNR of at least 0.37 is an independent predictor of DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…Only one of the previous report identified NLR as an independent prognostic factor for disease-free survival 34 . However, these two reports showed that NLR was not an independent prognostic factor in survival 34,42 . As far as we know, this report is the first to show that PLR was a significant prognostic factor for survival.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Only one of the previous report identified NLR as an independent prognostic factor for disease-free survival 34 . However, these two reports showed that NLR was not an independent prognostic factor in survival 34,42 . As far as we know, this report is the first to show that PLR was a significant prognostic factor for survival.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, only two previous reports evaluated NLR in perihilar cholangiocarcinoma 34,42 . Only one of the previous report identified NLR as an independent prognostic factor for disease-free survival 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies demonstrated a significant correlation between GPS/modified GPS and the survival of patients with extrahepatic bile duct cancer following surgical resection [12, 13]. However, controversies still exist regarding the prognostic value of NLR in cholangiocarcinoma [8-12, 26]. Likewise, conflicting survival data are present regarding PLR in cholangiocarcinoma patients [10, 12, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil counts, lymphocyte counts, platelet counts, elevated C-reactive protein (CRP) levels, and hypoalbuminemia have been converted to ratios or scores, such as the neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR), and Glasgow Prognostic Score (GPS) [6], which have frequently been associated with the prognosis of solid tumors [5-7]. However, there are conflicting survival data regarding preoperative hematological inflammatory parameters in cholangiocarcinoma [8-14]. …”
Section: Introductionmentioning
confidence: 99%